On the Hump-Shaped Output Effect of Monetary Policy in an Open Economy - Christian Pierdzioch; Serkan Yener (Kiel Institute for World Economics (IfW), 2004)
Results of empirical research have revealed a characteristic hump-shaped effect of monetary policy shocks on output: the effect builds to a peak after several months and then gradually dies out. We analyze, in the context of a "new open economy macroeconomics" model, factors that imply a hump- shaped effect of a monetary policy shock on output. We find that a hump- shaped effect of output is likely to result if the model features a "catching up with the Joneses" effect, pricing-to-market behavior of firms, and imperfect international financial market integration.
Keywords: F31; F32; F41; 330; Monetary policy; Catching up with the Joneses; Pricing-to-market; International financial markets; Geldpolitik; Schock; Gesamtwirtschaftliche Produktion; Neue Makroökonomik offener Volkswirtschaften; Theorie